Tryptophan and Kynurenine Pathway Metabolites in Animal Models of Retinal and Optic Nerve Damage: Different Dynamics of Changes - Fiedorowicz, Michal; Choragiewicz, Tomasz; Thaler, Sebastian; Schuettauf, Frank; Nowakowska, Dominika; Wojtunik, Kamila; Reibaldi, Michele; Avitabile, Teresio; Kocki, Tomasz; Turski, Waldemar A.; Kaminska, Agnieszka; Grieb, Pawel; et al. (Frontiers in Physiology, 2019)
Kynurenines, products of tryptophan (TRP) metabolism, display neurotoxic (eg. 3-hydroxykynurenine; 3-HK) or neuroprotective (eg. kynurenic acid; KYNA) properties. Imbalance between the enzymes constituting the kynurenine pathway (KP) plays a role in several disease, including neurodegeneration. In this study, we track changes in concentrations of tryptophan and its selected metabolites after damage to retinal ganglion cells and link this data with expression of KP enzymes. Brown-Norway rats were subjected to intravitreal N-methyl-D-aspartate (NMDA) injection or partial optic nerve crush (PONC). Retinas were collected 2 and 7 days after the completion of PONC or NMDA injection. Concentrations of TRP, kynurenine (KYN) and KYNA were determined by high performance liquid chromatography (HPLC). Data on gene expression in the rat retina were extracted from GEO, public microarray experiments database. Two days after NMDA injection concentration of TRP decreased, while KYN and KYNA increased. At day 7 compared to day 2 decrease of KYN, KYNA and further reduction of TRP concentration were observed, but on day 7 KYN concentration was still elevated when compared to controls. TRP concentration was higher in PONC group than in controls. However, both KYN and KYNA was lower. At day seven concentration of TRP and KYN was higher, whereas concentration of KYNA declined. After intraorbital optic nerve crush downregulation of KyatI and KyatIII between 24 hours and 3 days after procedure was observed. Kmo expression was transiently upregulated (12 hours after the procedures). After intraorbital optic nerve transsection (IONT) Kmo expression was upregulated after 48 hours and 7 days, KyatI and KyatIII were downregulated after 12, 48 hours, 7 days and upregulated after 15 days. In vivo experiments showed that retinal damage or optic nerve lesion affect TRP metabolism via KP. However, the pattern of changes in metabolite concentrations was different depending on the model. In particular, in PONC KYNA and KYN levels were decreased. These observations correspond with data on expression of genes encoding KP enzymes assessed after optic nerve crush or transection.